’Small Gold Mine of Talent’: Integrating Prague Spring Refugee Professionals in Canada, 1968-1969 - Raska, Jan (Refuge: Canada’s Journal on Refugees, 2021)
Following the August 1968 Soviet-led invasion of Czechoslovakia, 11,200 Prague Spring refugees were resettled in Canada. This movement included many experienced professionals and skilled tradespeople. This article examines how these refugees navigated language training and barriers to employment, including professional accreditation, and examines how this experience shaped bureaucratic and public views of refugee integration. The focus of this article is primarily on resettlement and integration efforts in Ontario, since roughly half of the Prague Spring refugees were permanently resettled in the province. The article outlines how, as part of its efforts to help the refugees with their economic and social integration, Canadian officials provided assisted passage, initial accommodations, help with securing Canadian employment, and English- or French-language training. Prague Spring refugees navigated professional obstacles, including securing accreditation of their foreign credentials and underemployment in their respective fields. Their successful resettlement and integration depended on intergovernmental cooperation between Canada and its provinces, and the assistance provided by local Czech and Slovak communities across the country.